Comparison between cytomegalovirus and HIV viral load among HIV patient who underwent antiretroviral therapy - Tulle, Andrew; Santosaningsih, Dewi; Hastuti, Nurima Diyah Puji (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2025)
Introduction: Cytomegalovirus (CMV) is one of the most prevalent viral infections in humans. The prevalence is approximately 20 percent among children and nearly 100 percent among adults. Among immunocompetent individuals, CMV infection remains predominantly asymptomatic. However, in immunocompromised patients such as people with HIV (PWH), it can cause end-organ diseases that may be life-threatening. With the increasing administration of antiretroviral therapy (ART), HIV infection can be controlled, and complications from CMV infection have been decreasing. One critical method for monitoring CMV infection is identifying CMV viremia. This study aims to investigate whether CMV viremia persists in PWH undergoing ART and to explore its relationship with HIV viral load. The research seeks to provide insights to guide clinical management of CMV reactivation in this patient population Methods: This cross-sectional study analysed archived plasma samples to detect and compare CMV viral load and HIV viral load among PWH undergoing ART. The samples were archived biological materials collected for HIV viral load detection. All samples were previously tested by PCR to detect CMV. Data were analysed using the Mann-Whitney test and Spearman correlation test. Result: Among 67 total samples, seven were identified as CMV positive, displaying various viral load concentrations. Analysis using the Mann-Whitney test demonstrated a statistically significant difference between variables, while the Spearman correlation test showed no correlation between them. This indicated that CMV viremia may not be directly influenced by HIV infection. Conclusion: Despite the significant difference between variables, the CMV viral load among PWH undergoing ART was not correlated with HIV viral load status. These findings suggest that CMV monitoring should be considered independently of HIV viral load status. However, the limited sample size suggests caution in generalizing these findings.